Wireless Enabled Voice over Internet Protocol (VoIP) Network Application Using Asterisk PBX - Narte Odjidja, Euclid; Kabanda, Salah; Akotam Agangiba, William; Kofi Annan, Richard (EAI Endorsed Transactions on Internet of Things, 2018)
This paper reechoes the need to use VOIP-based communication channels in order to reduce the heavy cost burden of communication in Sub Saharan Africa and other developing countries. We focus specifically on the context of the campus environment and implement IP PBX to cut down the cost of placing and receiving voice calls, instant messaging and voice mails with other colleagues connected to an Asterisk server on WIFI-enabled networks. We are motivated by the ease and cost-effectiveness of setting up WIFI-enabled IP network infrastructure which in recent times could be extended to allow inter-institutional linkage to allow collaboration and research.